Multiplex CRISPR-Cas9 editing of DNA methyltransferases in rice uncovers a class of non-CG methylation specific for GC-rich regions. Issue 9 (12th June 2021) - Hu, Daoheng; Yu, Yiming; Wang, Chun; Long, Yanping; Liu, Yue; Feng, Li; Lu, Dongdong; Liu, Bo; Jia, Jinbu; Xia, Rui; Du, Jiamu; Zhong, Xuehua; et al.
Abstract: DNA methylation in the non-CG context is widespread in the plant kingdom and abundant in mammalian tissues such as the brain and pluripotent cells. Non-CG methylation in Arabidopsis thaliana is coordinately regulated by DOMAINS REARRANGED METHYLTRANSFERASE (DRM) and CHROMOMETHYLASE (CMT) proteins but has yet to be systematically studied in major crops due to difficulties in obtaining genetic materials. Here, utilizing the highly efficient multiplex CRISPR-Cas9 genome-editing system, we created single- and multiple-knockout mutants for all the nine DNA methyltransferases in rice ( Oryza sativa ) and profiled their whole-genome methylation status at single-nucleotide resolution. Surprisingly, the simultaneous loss of DRM2, CHROMOMETHYLASE3 (CMT2), and CMT3 functions, which completely erases all non-CG methylation in Arabidopsis, only partially reduced it in rice. The regions that remained heavily methylated in non-CG contexts in the rice Os-dcc ( Osdrm2 / cmt2 / cmt3a ) triple mutant had high GC contents. Furthermore, the residual non-CG methylation in the Os-dcc mutant was eliminated in the Os-ddccc ( Osdrm2 / drm3 / cmt2 / cmt3a / cmt3b ) quintuple mutant but retained in the Os-ddcc ( Osdrm2 / drm3 / cmt2 / cmt3a ) quadruple mutant, demonstrating that OsCMT3b maintains non-CG methylation in the absence of other major methyltransferases. Our results showed that OsCMT3b is subfunctionalized to accommodate a distinct cluster of non-CG-methylated sites at highly GC-rich regions in the rice genome. Abstract : Examination of knockout mutants reveals that rice methyltransferases have subfunctionalized to accommodate a distinct cluster of non-CG-methylated sites at highly GC-rich regions in the rice genome.